Litteraturens kritik. Franz Kafka og den kritiske sensibilitet - Holm, Isak Winkel (K&K - Kultur og Klasse, 2016)
The article discusses the usefulness of the concept of critique for the understanding of the relation between literature and politics. Exploring two recent books about the political dimension of Franz Kafka’s literary works – Vivian Liska’s When Kafka Says We: Uncommon Communities in German-Jewish Literature (2009) and Michael Löwy’s Franz Kafka: rêveur insoumis (2004) – the article distinguishes between two different understandings of critique: critique of ideology and post-structuralist critique. In Liska’s and Löwy’s interpretations of Kafka, these two standard understandings of critique are unable to grasp the critical potential of Kafka’s literary works in general and of Kafka’s short story “Fellowship” from 1920 in particular. Instead, based on Jacques Rancière’s concept of ‘dissensus’, the article puts forward a concept of critique based on the reader’s aesthetic experience of Kafka’s literary works.